The Interplay between Habitus, Social Variables and Occupational Preferences - Vilhjalmsdottir, Gudbjörg [Verfasser]; Arnkelsson, Gudmundur [Verfasser] (My University, 2003)
"European researchers haverecently introduced Bourdieu's habitus theoryand research methods into the research field ofcareer development. The advantage of Bourdieu'stheory is to overcome the theoretical problemsthat in this field have resulted from overemphasis on individual aspects of careerdevelopment at the expense of social aspects.The habitus concept allows for the dichotomybetween the individual and the socialdimensions to be overcome. The researchreported here looks at the interplay betweenhabitus, social variables and careerpreferences but in a younger age group than haspreviously been studied. It also wonderswhether habitus groups exist in the relativelyhomogenous population of Iceland at arelatively young age, i.e., before divergence inthe educational system. Analyses resulted in five habitus groups beingformed on the basis of endorsement of culturaland leisure activities. Furthermore, the fivegroups differed both in terms of sexcomposition and - importantly - of preferredfuture occupations. It was concluded thathabitus groups form readily and have importantimplications for research and practice withinthe field of career counselling. " (author's abstract, IAB-Doku) ((en))
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; S 1.1 Allgemeinbildende Schule; T 2.3 Handlungstheorien; I 2.2.1 Westeuropa; Berufswahlmotiv; Schulwahl; Persönlichkeitsmerkmal; Soziale Faktoren; Handlungstheorie; Berufsberatung; Island